2018
DOI: 10.1016/j.ejso.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A population-based audit of surgical practice and outcomes of oncoplastic breast conservations in Scotland – An analysis of 589 patients

Abstract: This study demonstrated that measured outcomes of OBC in a population-based multi-centre setting can be comparable to the outcomes of large volume single centre series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 42 publications
(85 reference statements)
3
19
0
Order By: Relevance
“…This is consistent with several other previous studies [8,17e19]. A trend towards a higher risk of reoperation in the DCIS group (15.1%) and in the invasive lobular carcinoma group (12.3%) was observed, as reported earlier [8,11,20], yet this did not reach statistical significance (p ¼ 0.007).…”
Section: Resection Margins and Reoperationssupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with several other previous studies [8,17e19]. A trend towards a higher risk of reoperation in the DCIS group (15.1%) and in the invasive lobular carcinoma group (12.3%) was observed, as reported earlier [8,11,20], yet this did not reach statistical significance (p ¼ 0.007).…”
Section: Resection Margins and Reoperationssupporting
confidence: 92%
“…This is comparable to other studies. Romics et al [11] reported a LR rate of 2.7% during a median of 30 months follow-up, Clough et al a LR rate of 2.2% during a median of 55 months follow-up [8] and Rietjens at al. [9] a LR of 3.4% during a median of 74 months follow-up.…”
Section: Local Recurrencesmentioning
confidence: 97%
“…Oncoplastic breast conservation surgery has been shown as a safe alternative to mastectomy and immediate breast reconstruction in selected patients based on the combined data of iBRA-2 and TeaM studies of 2916 patients (17). Further, the Scottish audits of oncoplastic breast conservations indicate that oncoplastic surgery can widen the indications for breast conservation, and provide good oncological outcome with low complication rates in our hands, hence it can be a reasonable alternative to mastectomy with immediate reconstruction (18)(19)(20)(21). One unit in Italy did offer immediate breast reconstruction even during the peak of the COVID-19 pandemic as it is indicated by Fragetti et al who reported 15 nipple-sparing mastectomies with immediate J o u r n a l P r e -p r o o f reconstruction done in 13 patients, although reconstructive techniques were not disclosed (14).…”
Section: Discussionmentioning
confidence: 99%
“…Mastectomy rates were different according to histological types of tumor: 49.7% (1,960/3,942, 95% CI 48.1–51.3) for DCIS,1,46,8,11,13,14 50.9% (9,446/18,566, 95% CI 50.2–51.6) for invasive BC, 55.7% (95% CI 54.5–56.9) for ductal invasive BC, 70.5% (95% CI 68.3–72.7) for lobular invasive BC, and 60.9% (95% CI 57.8–64.0) for other invasive histological types 2…”
Section: Discussionmentioning
confidence: 99%